Ventilatory Support in Persistent Pulmonary Hypertension of the Newborn - Esther Jurfest Ceccon, Maria; Brunow de Carvalho, Werther (Current Respiratory Medicine Reviews, 2012)
Objective: Present a review about the use of mechanical pulmonary ventilation in Hypertension Pulmonary Persistent Neonatal (HPPN), the conventional mode and the indication of high-frequency oscillatory ventilation (HFOV). Also present other approaches, such as therapeutics use of exogenous surfactant, inhaled nitric oxide, phosphodiesterases inhibitors and extracorporeal membrane oxygenation. Data Source: It has been used in articles obtained in the Pub Med, Medline, Cochrane BVS, databases, in which there are topics about mechanical ventilation in Hypertension Pulmonary Persistent Neonatal and others treatments used in the newborn with HPPN. Conclusion: The effective treatments used in HPPN are a conventional, not very aggressive ventilatory strategy; HFOV; inhaled nitric oxide and vasodilators medications that act on the lungs rather than on the whole system, and, in newborns that do not respond to these treatments, the use of extracorporeal membrane oxygenation.
Keywords: high-frequency oscillatory ventilation